PENYULUHAN TENTANG STRUKTUR ORGANISASI FORMAL PADA REMAJA MASJID DARUL MUTTAQIN BEDOG, DESA DONOTIRTO, KECAMATAN KRETEK, KABUPATEN BANTUL, D.I.Y. - Burhanudin - (Adi Widya : Jurnal Pengabdian Masyarakat, 2021)
One of the problems faced by mosque youth is organizational and management problems. This is due to their low knowledge or understanding of organization and management. As a result, mosque youth cannot play an active role in participating in the prosperity of the mosque, namely by holding positive activities. This counseling was carried out to provide basic knowledge about organization and management to mosque youth, especially regarding formal organizational structures. This community service is carried out by extension methods, which are accompanied by discussion or question and answer. The counseling was carried out to the teenagers of the Darul Muttaqin Bedog mosque, Donotirto, Kretek, Bantul, Yogyakarta Special Region.